Cloud services as contemporary tool of educational institution management - I. V. Plish (Academy of Cognitive and Natural Sciences, 2014)
Research aim: to highlight the experience of using cloud services in the management of a general educational institution. Research task: substantiation of the prospect and availability of the use of modern information technologies in the work of the school principal. Object of research: cloud services as a modern tool in the management of an educational institution. Subject of research: cloud services as a modern tool in the management of the educational institution Specialized school-kindergarten «Lisova kazka». Research methods: source analysis, synthesis. Research results: schematically represent the interconnections of the main blocks of the system, which is effectively implemented in the activities of the director of the «Lisova kazka» in recent years. The experience of using cloud services in educational institution management is described in this stuff. The main target of this work is displaying of perspective using state-of-art IT solutions in head teachers work. The experience of using Basecamp system project management, which gives an opportunity of continual support management activity, provides permanent feedback link with teaching staff, process control of set missions and necessity of real-time correcting etc. The system of management allows head teacher, teaching staff and supporting services to use the resources of the named above system independently from their location using any gadget or personal computer and it doesn't matter what software is installed. The author presents schematically the interlinks of main system blocks that has been integrated effectively in head teacher's work recent years.